STUDI KOMPARASI PENGEMBANGAN KARIR KARYAWAN DITINJAU DARI PERSPEKTIF KINERJA DAN SENIORITAS PADA PDAM GIRI MENANG MATARAM - Irwan Cahyadi; Abdurrahman Abdurrahman; Isra Dewi Kuntary Ibrahim (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2023)
One of the goals of an employee working in a company is to get career development. However, there is often a bias towards indicators of career development in Indonesia in general, namely career development based on performance or seniority. The purpose of this research is to find out which factors are more dominant between performance and seniority which form the basis for career development decisions in PDAM Giri Menang Mataram. This type of research is included in associative research using survey methods in collecting data. The analytical tool used is t-test analysis at 5% alpha. Based on the results of the t test, it is known that the more dominant factor that forms the basis for career development decisions at PDAM Giri Menang Mataram is employee performance.